Signal Transduction by Reactive Oxygen and Nitrogen Species pathways and chemical principles - Forman, Henry Jay;Ed. Fukuto, Jon;Ed. Torres, Martine;Ed (Kluwer Academic Publishers, 2003)
This exciting area of research will benefit from the pulling together of the work from hard-core chemists and free radical aficionados along with that of signaling enthusiasts and cell biologist devotees. This was the idea behind the conception of this new book. Signal Transduction by Reactive Oxygen and Nitrogen Species: Pathways and Chemical Principles provides relevant chemistry that can be applied across signaling systems and summarizes the current state of knowledge in the area of redox signaling, including controversies when they exist and future directions. ROS and RNS have been implicated in inflammation, aging and cancer and their novel role in signal transduction may offer new clues to their participation in these processes. This volume should be of great interest to researchers involved in a large range of scientific fields from biochemistry and physiology to pharmacology.